Effect of Temperature on the Dynamic Properties of Mixed Surfactant Adsorbed Layers at the Water/Hexane Interface under Low-Gravity Conditions - Volodymyr I. Kovalchuk; Giuseppe Loglio; Alexey G. Bykov; Michele Ferrari; Jürgen Krägel; Libero Liggieri; Reinhard Miller; Olga Yu. Milyaeva; Boris A. Noskov; Francesca Ravera; Eva Santini; Emanuel Schneck (Colloids and Interfaces, 2020)
An increase in temperature typically leads to a decrease in the interfacial tension of a water/oil interface. The addition of surfactants to the system can complicate the situation significantly, i.e., the interfacial tension can increase or decrease with an increasing temperature. For most concentrations of the two studied surfactants, the cationic tetradecyl trimethyl ammonium bromide (TTAB) and the nonionic tridecyl dimethyl phosphine oxide (C13DMPO), the measured interfacial tension of the aqueous mixed surfactant solutions against hexane increases when the temperature decreases between 30 °C and 20 °C. However, with a further temperature decrease between 20 °C and 15 °C, the reverse effect has also been observed at some concentrations, i.e., a decrease of interfacial tension. Additionally, the corresponding dilational interfacial visco-elasticity shows some discrepant temperature effects, depending on the bulk concentration and oscillation frequency. The experiments have been performed with a capillary pressure tensiometer under the conditions of micro-gravity. The reason for the positive and negative interfacial tension and visco-elasticity gradients, respectively, within certain ranges of the temperature, concentration and mixing ratios, are discussed on the basis of all available parameters, such as the solubility and partitioning of the surfactants in the two liquid phases and the oscillation frequency.